2022
DOI: 10.1111/eea.13132
|View full text |Cite
|
Sign up to set email alerts
|

Ecological trade‐offs in development and defence in a specialist moth when feeding on four congeneric host plants

Abstract: Understanding herbivore diet breadth is fundamental for understanding the evolution of biodiversity, particularly in the tropics where the diversity of plant-herbivore interactions is believed to be responsible for a large part of global biodiversity (Novotny et al., 2006;Dyer et al., 2007). The study of host plant use by herbivorous insects was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Crotalaria pallida and E. zinckenella are known to interact throughout the Americas, where C. pallida is exotic (Segarra‐Carmona & Barbosa 1990). It is possible that E. zinckenella is more restricted to C. pallida , while U. ornatrix can use a range of different Crotalaria species (Pareja 2022), and could suggest that the importance of different herbivores will vary spatially. Therefore, different herbivores could act as keystone herbivores in different communities that vary in plant species composition (Poelman & Kessler 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Crotalaria pallida and E. zinckenella are known to interact throughout the Americas, where C. pallida is exotic (Segarra‐Carmona & Barbosa 1990). It is possible that E. zinckenella is more restricted to C. pallida , while U. ornatrix can use a range of different Crotalaria species (Pareja 2022), and could suggest that the importance of different herbivores will vary spatially. Therefore, different herbivores could act as keystone herbivores in different communities that vary in plant species composition (Poelman & Kessler 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For toxic plant generalists, there may often be a trade-off between the nutritional quality of a potential food and the availability of toxins for sequestration (i.e. highly nutritional foods often do not contain toxins for sequestration) [5,[8][9][10][11]. It has been well demonstrated that, when faced with such a tradeoff, toxic plant generalists engage in diet mixing, yielding protection from parasitism or predation [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…For toxic plant generalists, there may often be a trade-off between the nutritional quality of a potential food and the availability of toxins for sequestration (i.e., highly nutritional foods often do not contain toxins for sequestration) (Ballabeni et al, 2001;Pareja, 2022;Rodrigues et al, 2010;Rodrigues & Freitas, 2013;Singer et al, 2004). We hypothesized that toxic plant generalists engage in diet mixing between nutritionally superior non-toxic foods and nutritionally inferior toxic foods to balance nutrition and defense.…”
Section: Introductionmentioning
confidence: 99%